The Effect of Value Added Tax on Public Purchasing Power: Quantitative Analysis of Consumers of Goods and Services in Indonesia (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study investigates the impact of Value Added Tax (VAT) on the purchasing power of Indonesian consumers through a quantitative research approach. Utilizing secondary data sourced from the Central Statistics Agency for the period 2018–2023, the analysis incorporates key economic indicators such as the inflation rate, consumer price index, and household consumption levels. The research sample comprises 1,250 respondents from five major urban centers in Indonesia, providing a diverse representation of consumer behavior across regions. The analytical method employed is multiple linear regression, with the VAT rate as the independent variable and purchasing power as the dependent variable, measured using the consumer purchasing power index. The results reveal a statistically significant negative correlation (r = -0.732, p < 0.05) between VAT increases and consumer purchasing power. Specifically, the study finds that a 1% rise in the VAT rate corresponds to a 2.4% decline in purchasing power, indicating a substantial sensitivity of household consumption to fiscal policy adjustments. These findings underscore the critical role of VAT policy in shaping consumer economic behavior and highlight the potential adverse effects of indiscriminate tax increases on household welfare. The study recommends that fiscal authorities adopt a more selective and targeted approach in determining VAT rates, particularly during periods of economic volatility or inflationary pressure. Such measures are essential to preserve consumer confidence, maintain economic stability, and support equitable growth. By providing empirical evidence on the relationship between taxation and consumer welfare, this research contributes to the broader discourse on fiscal policy effectiveness in emerging economies. It offers actionable insights for policymakers seeking to balance revenue generation with social and economic resilience in the face of evolving macroeconomic challenges.